ANALISA DAMPAK LALULINTAS AKIBAT PEMBANGUNAN RUKO DAN GUDANG DI JALAN RAYA KEMANGSEN KECAMATAN BALONGBENDO SIDOARJO - Muhammad Shofwan Donny; R Endro Wibisono (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2020)
The plan to build shophouses and warehouses located at Jalan Raya Kemengsen Sidoarjo, will cause traffic movement which will result in a decrease in road performance. For this reason, it is necessary to calculate the Traffic Impact (Andalalin) study in order to continue to provide a good level of service on the road section, as well as to provide a solution to the traffic problems that occur due to the construction of the shop and warehouse. The method used in this study is based on the Indonesian Road Capacity Manual (MKJI 1997). The initial stage of the research method is the traffic survey then calculates the traffic flow and determines the andalalin classification. After that, calculate the traffic performance in the existing conditions in 2019 and calculate the year forecasting due to the construction of shophouses and warehouses in 2025. The results of this study show the performance of the existing traffic on the Kemengsen and Mayjen Bambang Yuwono Highway with a DS value reaching 0.52 service levels C. While the traffic performance in 2025 is DS = 0.84 or level of service D. An alternative offered to improve road services is the addition of road width and the provision of parking spaces.